Rigid‐Flexible Hybrid Porous Molecular Crystals with Guest‐Induced Reversible Crystallinity. (15th February 2023) - Wang, Danbo; Zhao, Yingjie
Abstract: A weak CH/O hydrogen‐bonded organic framework (HOF) with both rigidity and flexibility that could easily and reversibly switch from a non‐crystalline to a crystalline phase was constructed. The specific solvent molecule acts as a "key" to control the crystallinity, while the highly rigid triangle macrocycle as the building block is the "lock". The introduction and removal of the "key" could influence the local flexibility of the whole framework and lead to switchable crystallinity. Furthermore, the obtained HOF exhibits excellent separation efficiency for benzene and cyclohexane (94.4 %). Abstract : A globally robust HOF with both rigidity and flexibility was constructed. The non‐crystalline and crystalline phases of the HOF could be easily and reversibly switched at will with the specific solvent molecule. Furthermore, the obtained HOF exhibits excellent separation efficiency for benzene and cyclohexane (94.4 %).